IMPLEMENTASI KEBIJAKAN PENGELOLAAN RUMAH SUSUN SEDERHANA SEWA KALIGAWE SEMARANG - Pramesta, Lendhia Maharani; Subowo, Ari; Kismartini, Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The city of Semarang, as an urban area, is not free from the problems of population density, slums and squatter settlements. Rusunawa Kaligawe was built to provide livable and affordable housing for MBR (Low Income Communities). The current condition is no longer suitable for the purpose of providing flats, namely providing adequate housing for MBR. Rusunawa Kaligawe is less than optimal in management, thus leading to a decline in the quality of housing. The aim of this research is to analyze the implementation of Rusunawa management policies and analyze the factors related to the implementation of Rusunawa management policies. The research method used is descriptive qualitative. The management of the Kaligawe Rusunawa has not been effective because it has not created adequate housing. Efficiency has not been achieved, the government has not been able to provide adequate housing from the budget provided, so management has not been able to achieve maximum effectiveness. Based on the physical environmental conditions and the role of institutions, it is not enough to provide adequate housing in Kaligawe Flats. However, judging from its connection with other areas, the location of Rusunawa Kaligawe is a strategic area. Residential units in Rusunawa Kaligawe can be distributed evenly to the target group, but there has been a change of ownership. The responsiveness of Rusunawa management has not been achieved because it has not been able to satisfy the residents and there has never been a social empowerment program from the management.